Pengembangan Lembar Kerja Peserta Didik Gerak Jatuh Bebas Bermuatan STEM (Science, Technologi, Engineering, And Mathematics) Untuk Meningkatkan Keterampilan Generik Sains Kelas X - Setiawan, Didik; Supriyadi, Supriyadi; Ellianawati, Ellianawati (Universitas PGRI Semarang, 2022)
Learning related to STEM aspects provides opportunities for students to understand the concept of Physics combined with technology, engineering and mathematics through discussion, practicum, and project making activities. Learning physics has four main components that must be achieved by students. The four components are understanding, skills, abilities and scientific attitudes. These abilities are basic abilities that are included in the generic science skills that need to be analyzed for their development in students. This study aims to determine student responses to the development of STEM-charged free fall worksheets that can improve generic science skills for class X. This study uses descriptive research methods to determine student responses to the development of learning media. The results of this study based on interviews with physics teachers that the LKPD did not contain STEM which improved science generic skills and showed that the STEM-loaded LKPD media for use in learning received a student response of 79.9% with a good category.Keywords: LKPD, STEM, science generic skills